KAIZEN COSTING UNTUK MENINGKATKAN KEPUASAN PELANGGAN PADA UMKM (STUDI KASUS: KEDAI KOPI UNCLEBREW JAKARTA) - Antika Rizki Utami Permadi; Lely Dahlia (Universitas Kristen Krida Wacana, 2021)
The purpose of this study was to analyze the application of kaizen costing at Unclebrew Coffee Shops to customer satisfaction. The population of this research is the buyers of Unclebrew Coffee Shop Jakarta. The sampling technique used convenience sampling. The result of this study prove that partially the variables Seiri, Seiton, Seiketsu and Shitshuke influence in customer satisfaction, while Seiso no effect on influence customer satisfaction, but simultaneously all the variables Seiri, Seiton, Seiso, Seiketsu and Shitshuke have an effect on customer satisfaction. Keywords: Customer Satisfaction, Kaizen Costing, UMKM